Aspects of serrated flow in aluminium alloys - Robinson, Jonathan Mark (Centre for Materials Engineering, 2017)
Uniaxial tensile testing has been undertaken on a range of aluminium base alloys. Material investigated included commercial binary Al-Mg (5182), ternary Al-Mg-Si (6061) and quaternary Al-Cu-Mn-Si (2014) as well as experimental alloys containing 2at.% additions of Ag, Mg and Zn to commercially pure AI (1070). In addition, composite materials based on both alloys 2014 and 6061, containing 10%, 15% and 20% additions of Ah03 particulate, as well as 20% SiC particulate in the case of 6061, were also tested. Microstructures of materials were varied by prior heat treatments but, for comparison, all materials, were initially tested in the solution treated and quenched condition. Mechanical testing was undertaken at room temperature throughout the course of the work, and at strain rates such that serrated tensile test curves were manifest. The evolution of microstructural features of the deformation was evaluated utilising both optical and electron microscopy. Surface deformation features, including the formation of both type A and type B deformation markings, was examined on pre-polished specimen gauge lengths at various levels of tensile strain. The planarity of slip line traces was correlated with the evolution of related deformation structures in dynamic experiments in a high voltage transmission electron microscope (HVEM). In addition, the formation of slip lines on the surface of the HVEM microtensile specimens compared favourably with those formed on the surfaces of macroscopic tensile specimens. Microscale heterogeneities in the deformation observed during in-situ dynamic HVEM experiments on poly crystalline material correlated with the extent of serrated flow manifest in bulk specimens. All materials deformed in the HVEM displayed inhomogeneous dislocation motion consistent with the macroscopically observable discontinuities. The alloys tested were microstructurally distinguishable during dynamic experiments depending primarily on whether or not they had been deliberately alloyed with magnesium. The alloys containing Mg exhibited the activation of parallel slip traces together with minimal cross-slip in any single micro-yield event. In contrast, the alloys which did not contain Mg exhibited the simultaneous activation of various intersecting slip systems and were characterised by extensive cross-slip during similar yield events. On the basis of these observations, the magnitude of serrations and extent of serrated flow in the alloys has been discussed. The extent to which the different alloys were able to undergo dynamic recovery affected both the evolution of the dislocation structure observed in the conventional transmission electron microscope ( CTEM) as well as the final fracture mode. The existence of a characteristic shear fracture mode was consistently observed to follow tensile deformation which had been dominated by unstable plastic flow. The ready occurrence of dynamic recovery and the associated formation of dislocation cell structures allowed for more fully developed plastic instability during the final stages of tensile deformation and a lower likelihood of final failure by premature shear. Finally, the addition of particulate reinforcement to 2014 and 6061 had different effects that were accounted for by the difference in strength between the two monolithic materials. In the case of the weaker 6061, all particulate additions had a strengthening effect whereas in 2014, increasing the volume percent of reinforcement progressively weakened the composite. Serrated flow properties of both alloys were affected by the addition of the particulate reinforcement. The homogeneity of particle distribution as well as the size of the particulate inclusions affected both the tensile properties and final fracture of the composites.